Kompetencja językowa i komunikacyjna dzieci z zaburzeniami słuchu w kontekście wzorca gatunkowego SMS-a - Jachimowska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article describes the methods of the SMS genre use, emphasising language competency (system proficiency) and communication competency (including pragmatic competency) of the tested group. The author presents the results of tests performed on a group of children with hearing disability (with various rate and type of hearing disability) aged 12–16 and confronts the results with the results achieved in the group of children without hearing issues (development norm). The article attempts to determine the mutual relations between language and communication competency acquisition by children with hearing disability and their genre competency. Short Message Service (SMS) was used as an example genre.